2007
DOI: 10.1073/pnas.0709307104
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of zinc transporter ZIP4 (SLC39A4) significantly contributes to human pancreatic cancer pathogenesis and progression

Abstract: Zinc is an essential trace element and catalytic/structural component used by many metalloenzymes and transcription factors. Recent studies indicate a possible correlation of zinc levels with the cancer risk; however, the exact role of zinc and zinc transporters in cancer progression is unknown. We have observed that a zinc transporter, ZIP4 (SLC39A4), was substantially overexpressed in 16 of 17 (94%) clinical pancreatic adenocarcinoma specimens compared with the surrounding normal tissues, and ZIP4 mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
257
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(271 citation statements)
references
References 28 publications
9
257
2
3
Order By: Relevance
“…Instead, they relied on their identification of an increase in ZIP4 in ductal adenocarcinoma, and on experimental studies with cell lines, genetically manipulated cells, and with an animal model. 6,16 However, the increase in ZIP4 in situ in the ductal adenocarcinoma tissue section does not exhibit transporter association with the basilar membrane, which should be expected for a functional cellular zinc uptake transporter. No information regarding the stages of malignancy is provided in their study.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 83%
See 2 more Smart Citations
“…Instead, they relied on their identification of an increase in ZIP4 in ductal adenocarcinoma, and on experimental studies with cell lines, genetically manipulated cells, and with an animal model. 6,16 However, the increase in ZIP4 in situ in the ductal adenocarcinoma tissue section does not exhibit transporter association with the basilar membrane, which should be expected for a functional cellular zinc uptake transporter. No information regarding the stages of malignancy is provided in their study.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 83%
“…In the only other report relating to zinc and zinc transporter in normal exocrine pancreas and adenocarcinoma, Li et al 6 suggested that zinc is increased in human ductal adenocarcinoma and promotes the development of malignancy. However, they provided no data and/or information of zinc levels or measurements in human normal pancreas and in adenocarcinoma in structures, which is the focus of the normal and adenocarcinoma studies presented in this report.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in breast and prostate cancer cells with overexpression of zinc ion importers demonstrates that exposure to small amounts of ionic zinc can enhance cancer cell proliferation and invasion. 41,42 Lin et al identified several zinc ion importers with increased expression in malignant glioma samples and waterborne exposure of embryonic zebrafish to zinc can result in distribution to the brain. 43,44 Furthermore, invasion of glioblastoma cells is partly controlled by matrix metalloproteinases (MMPs), which require zinc as cofactor.…”
Section: Embryo-larval Zebrafish Xenograft Assay 325mentioning
confidence: 99%
“…Multiple zinc transporters, including ZIP4, ZIP6, ZIP10, and ZIP1, have been identified as factors in the progression of various types of cancer. ZIP4 has been reported to increase cell proliferation through zinc transport, resulting in tumor growth, most specifically in pancreatic cancer (44,55). Both ZIP6 and ZIP10 have roles in the progression and metastasis of breast cancer (46,(57)(58) and ZIP1 has been suggested as a tumor suppressor of prostate cancer (56).…”
mentioning
confidence: 99%